Harpacticoid Copepods in Sarawak Coastal Waters: Ecology, Taxonomy and Its Captive Culture Trials - Fatimah A’tirah, Binti Mohamad (unimas, 2017)
Study on zonation of harpacticoids in intertidal flat are being neglected since several decades because recent studies are more focused and interest in culture, experimental and bioassay of copepods. This study was conducted to investigate the zonation of harpacticoids in Buntal Beach by established two horizontal line transects. Different zonation distribution of harpacticoids were found on those two transects. Multidimensional scaling (nMDS) together with dendogram analysis showed moderate similarity of stations at Transect 1 while low similarity at Transect 2. BIOENV results demonstrated a highest rank correlation (ρ=0.631) between harpacticoids abundance and environmental variables (DO, temperature, TOM, chlorophyll a, skewness coefficient and sand (%)) at Transect 1 whereas harpacticoids density at Transect 2 primarily dependent on temperature. From April 2014 to March 2015, harpacticoids were sampled monthly together with in-situ interstitial water parameter and sediments samples for biological analyses. The study was conducted to determine the seasonal variations of harpacticoid copepods in Buntal Beach. The samplings were conducted in two random stations (Station A and Station B).